Seasonal and geographic variation in packed cell volume and selected serum chemistry of platypuses - Jana Stewart (Nature Portfolio, 2021)
Abstract Platypuses (Ornithorhynchus anatinus) inhabit the permanent rivers and creeks of eastern Australia, from north Queensland to Tasmania, but are experiencing multiple and synergistic anthropogenic threats. Baseline information of health is vital for effective monitoring of populations but is currently sparse for mainland platypuses. Focusing on seven hematology and serum chemistry metrics as indicators of health and nutrition (packed cell volume (PCV), total protein (TP), albumin, globulin, urea, creatinine, and triglycerides), we investigated their variation across the species’ range and across seasons. We analyzed 249 unique samples collected from platypuses in three river catchments in New South Wales and Victoria. Health metrics significantly varied across the populations’ range, with platypuses from the most northerly catchment, having lower PCV, and concentrations of albumin and triglycerides and higher levels of globulin, potentially reflecting geographic variation or thermal stress. The Snowy River showed significant seasonal patterns which varied between the sexes and coincided with differential reproductive stressors. Male creatinine and triglyceride levels were significantly lower than females, suggesting that reproduction is energetically more taxing on males. Age specific differences were also found, with juvenile PCV and TP levels significantly lower than adults. Additionally, the commonly used body condition index (tail volume index) was only negatively correlated with urea, and triglyceride levels. A meta-analysis of available literature revealed a significant latitudinal relationship with PCV, TP, albumin, and triglycerides but this was confounded by variation in sampling times and restraint methods. We expand understanding of mainland platypuses, providing reference intervals for PCV and six blood chemistry, while highlighting the importance of considering seasonal variation, to guide future assessments of individual and population condition.